Management of post-cholecystectomy biliary fistula according to type of cholecystectomy - Sultan, Ahmad M.; Elnakeeb, Ayman M.; Elshobary, Mohamed M.; El-Geidi, Ahmed A.; Salah, Tarek; El-hanafy, Ehab A.; Atif, Ehab; Hamdy, Emad; Elebiedy, Gamal K. (Endoscopy International Open, 2015)
Background and study aims: A study was undertaken to describe the management of post-cholecystectomy biliary fistula according to the type of cholecystectomy. Patients and methods: A retrospective analysis of 111 patients was undertaken. They were divided into open cholecystectomy (OC) and laparoscopic cholecystectomy (LC) groups.Results: Of the 111 patients, 38 (34.2 %) underwent LC and 73 (65.8 %) underwent OC. Endoscopic retrograde cholangiopancreatography (ERCP) diagnosed major bile duct injury (BDI) in 27 patients (38.6 %) in the OC group and in 3 patients (7.9 %) in the LC group (P = 0.001). Endoscopic management was not feasible in 15 patients (13.5 %) because of failed cannulation (n = 3) or complete ligation of the common bile duct (n = 12). Endoscopic therapy stopped leakage in 35 patients (92.1 %) and 58 patients (82.9 %) following LC and OC, respectively, after the exclusion of 3 patients in whom cannulation failed (P = 0 0.150). Major BDI was more commonly detected after OC (P < 0.001). Leakage was controlled endoscopically in 77 patients (98.7 %) with minor BDI and in 16 patients (53.3 %) with major BDI (P < 0.001).Conclusions: Major BDI is more common in patients presenting with bile leakage after OC. ERCP is the first-choice treatment for minor BDI. Surgery plays an important role in major BDI. Magnetic resonance cholangiopancreatogrphy (MRCP) should be used before ERCP in patients with bile leakage following OC or converted LC.